CCP encyclopedia of Philippine art. (Manila : Cultural Center of the Philippines, 1994)
Contents.- v.1-2. Peoples of the Philippines.-v.3. Architecture.-v.4. Visual arts.-v.5 Dance.-v.6. Music.-v.7. Theater.-v.8. Film.-v.9. Literature.-v.10. Index